2016
DOI: 10.1371/journal.pone.0150663
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Fires in Mediterranean Europe

Abstract: Forest fires are a serious environmental hazard in southern Europe. Quantitative assessment of recent trends in fire statistics is important for assessing the possible shifts induced by climate and other environmental/socioeconomic changes in this area. Here we analyse recent fire trends in Portugal, Spain, southern France, Italy and Greece, building on a homogenized fire database integrating official fire statistics provided by several national/EU agencies. During the period 1985-2011, the total annual burned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
137
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 51 publications
(73 reference statements)
12
137
1
4
Order By: Relevance
“…In the case of the Hinterland region, the trend in the number of fires suggests a higher frequency in winter. This behaviour was also found by Zavala et al (2011) andTurco et al (2016). The latter found an apparent shift in the mid-1980s, the same as we detected.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the case of the Hinterland region, the trend in the number of fires suggests a higher frequency in winter. This behaviour was also found by Zavala et al (2011) andTurco et al (2016). The latter found an apparent shift in the mid-1980s, the same as we detected.…”
Section: Discussionsupporting
confidence: 93%
“…However, the burned area shows a decrease in all regions and seasons. Previous studies by Rodrigues et al (2013), Spano et al (2014) and Turco et al (2016) have also found negative trends for a very similar time span. These works sug- Figure 5.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Indeed, results of several recent studies suggest a significant increase in the burnt area, not only in Portugal (Pereira et al, 2013) but also in the entire Iberian Peninsula (Sousa et al, 2015), for different scenarios of future climate and LULCC (Amato et al, 2018). These findings are in line with the fact that Portugal is the only European country where burnt area has not decreased in the last decades (Turco et al, 2016) and with the increase in the future fire danger for the Mediterranean Basin countries of Europe and north Africa (Bedia et al, 2014). In addition, burnt area in Portugal and in the Mediterranean Basin is clearly associated with extreme weather and climate variability, namely the occurrence of heat waves and drought (Amraoui et al, 2015;Pereira et al, 2005;Telesca and Pereira, 2010;Trigo et al, 2006Trigo et al, , 2016.…”
Section: Discussionsupporting
confidence: 59%